A Case of Metastatic Atypical Neuroendocrine Tumor with ALK Translocation and Diffuse Brain Metastases. (15th May 2017) - Wang, Victoria E.; Young, Lauren; Ali, Siraj; Miller, Vincent A.; Urisman, Anatoly; Wolfe, John; Bivona, Trever G.; Damato, Bertil; Fogh, Shannon; Bergsland, Emily K.
Abstract : A challenge in precision medicine requires identification of actionable driver mutations. Critical to such effort is the deployment of sensitive and well‐validated assays for mutation detection. Although identification of such alterations within the tumor tissue remains the gold standard, many advanced non‐small cell lung cancer cases have only limited tissue samples, derived from small biopsies or fine‐needle aspirates, available for testing. More recently, noninvasive methods using either circulating tumor cells or tumor DNA (ctDNA) have become an alternative method for identifying molecular biomarkers and screening patients eligible for targeted therapies. In this article, we present a case of a 52‐year‐old never‐smoking male who presented with widely metastatic atypical neuroendocrine tumor to the bones and the brain. Molecular genotyping using DNA harvested from a bone metastasis was unsuccessful due to limited material. Subsequent ctDNA analysis revealed an ALK translocation. The clinical significance of the mutation in this particular cancer type and therapeutic strategies are discussed. Abstract : A challenge in precision medicine is the identification of actionable driver mutations. Alterations can be identified within the tumor tissue, by small biopsy or fine‐needle aspirates, or by noninvasive methods, such as circulating tumor cells or circulating tumor DNA. This article presents a case of atypical neuroendocrine tumor metastatic to the bone and brain for which circulating tumor DNA analysis found an ALK translocation.